50 social studies strategies for K-8 classrooms - Obenchain, Kathryn M. (Pearson, 2011)
"A practical resource including 50 strategies for enhancing social studies teaching for elementary and middle school pre-service and practicing teachers alike. This popular book of 50 strategies for creating meaningful social studies experiences for K-8 students, often assigned to supplement traditional methods textbooks, now represents an even more valuable, cost and time-effective text for the course. Always appreciated for its connections between theory, research, and practice, and the extensions provided through web sites and references, this new edition enhances those strengths by providing assessment ideas and website resources for every strategy. Eight conceptually-organized overarching strategies to facilitate organizing a social studies classroom precede forty-two social-studies specific strategies--organized alphabetically and introduced by grade level and National Council for Social Studies (NCSS) standards indicators. This handy resource provides models, examples, and assessments from real teachers and students, so that pre-service teachers may be successful in their student teaching and field experiences and first years in the classroom and practicing teachers may freshen their social studies teaching with some new ideas."--Publisher's description.